War-Making and Mediation in Civil Wars: Three Ideal Types of Third Parties and Ripeness Concepts. Issue 2 (15th March 2022) - Iji, Tetsuro
ABSTRACT: Despite the accumulation of a sizable scholarship on mediation of civil war by third-party states, little effort has been made to formulate a conceptual framework geared toward explaining how the prior or ongoing modes of their engagements in war-making affect their possible conduct of mediation. The present article is an attempt to fill this lacuna by presenting a threefold typology of third-party states: war-making patrons, war-supporting friends, and war-observing bystanders. The article explores how these three kinds are distinct from one another as a mediator, in terms of such crucial aspects as motives and timing, readiness, bias and commitment, and leverage. This inquiry is pursued through extending to the level of third parties Zartman's seminal notions of a 'mutually hurting stalemate', a 'way out', and a 'mutually enticing opportunity' that have hitherto been discussed mainly at the level of primary parties. The article is intended as the presentation of an analytical framework and initial propositions rather than full-scale research results.